COLOR PSYCHOLOGY IN PAINTING AND ITS POSSIBILITIES OF ARTISTIC EXPRESSION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This scientific article comprehensively analyzes the theoretical foundations of color psychology in the art of painting, its connection with human emotions and perception, and the possibilities of artistic expression; the aesthetic, psychological, and semantic properties of color are highlighted using the examples of various historical periods and artistic movements, and the issues of expressing mood, mental state, and ideological content through color in a painting are scientifically substantiated; during the research, the pedagogical and creative significance of color psychology is revealed, and methodological recommendations for the conscious and purposeful use of color in the process of teaching painting are developed; the results of the article serve the theoretical and practical development of the art of painting, as well as improving the quality of art education.